1995
DOI: 10.1111/j.1467-8624.1995.tb00925.x
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocortical Responses to the Strange Situation in Infants with Disorganized/Disoriented Attachment Relationships

Abstract: Salivary cortisol levels were assessed in 19-month-old infants following the Ainsworth Strange Situation procedure. 38 infants participating in Project STEEP at the University of Minnesota served as subjects. Project STEEP is a longitudinal intervention program designed to promote healthy parent-child relationships and to prevent emotional problems among children born to mothers who are at high risk for parenting problems. Following the Strange Situation, saliva samples were collected and assayed for cortisol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
176
2
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(190 citation statements)
references
References 10 publications
9
176
2
3
Order By: Relevance
“…40 The nature and extent of overlap between attachment and temperament have been addressed by both theoretical and empirical studies. 41 There is empirical support for the contribution of both parenting behavior 42,43 and early temperament (eg, negative emotionality 44,45 or reactivity 46 ) to insecure and disorganized attachment, but the correlations are only small to moderate. Also, it is not clear what the causal relationships are among individual variations of temperament, parental behavior, and attachment quality.…”
Section: Discussionmentioning
confidence: 99%
“…40 The nature and extent of overlap between attachment and temperament have been addressed by both theoretical and empirical studies. 41 There is empirical support for the contribution of both parenting behavior 42,43 and early temperament (eg, negative emotionality 44,45 or reactivity 46 ) to insecure and disorganized attachment, but the correlations are only small to moderate. Also, it is not clear what the causal relationships are among individual variations of temperament, parental behavior, and attachment quality.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, higher cortisol levels were found for insecurely attached infants (Hertsgaard, Gunnar, Erickson, & Nachmias, 1995;Spangler & Grossman, 1993;Spangler & Schieche, 1998) and for infants with a combination of inhibited approach (e.g., to novelty of social situations) and insecure attachment (Gunnar, Brodersen, Nachmias, Buss, & Rigatuso, 1996;Nachmias, Gunnar, Mangelsdorf, Parritz, & Buss, 1996).…”
Section: Introductionmentioning
confidence: 94%
“…The pattern typically observed is one of decreasing cortisol levels from the beginning to 30 minutes after the end of the procedure. In contrast, studies examining disorganized patterns of attachment behavior have found that disorganized children produce larger increases in cortisol in response to separation and reunion than children classified as securely or insecurely attached [21,31]. In related work.…”
Section: Attachment Quality the Limbic Hypothalamic-pituitary-adrenomentioning
confidence: 99%